Covid-19 & the 2020 brazilian municipal elections : heterogenous effects of the fight against the pandemic on incumbency advantage using regression discontinuity designs - Mazza, Marcos (2023)
Fil: Mazza, Marcos. Universidad de San Andrés. Departamento de Economía; Argentina.